Living with mother alone: exploring the risk of stunting among under-five children in India - Barik, Soumen; Singh, Anuj; Singh, Mayank (Frontiers in Nutrition, 2025)
BackgroundStunting affects nearly one in three children under five in India. While socioeconomic, maternal, and environmental factors are well-established determinants, the role of household structure particularly children living with only their mother remains underexplored. Therefore, the present study aims to examine the association between family structure and stunting among children under 5 years of age in India. Specifically, the objective is to compare the risk of stunting among children living with their mothers only to those living with both parents and to identify the key factors contributing to any observed disparities.Data and methodsThis study analyzed data from 224,218 surviving children aged 0–59 months from the NFHS-5 (2019–21), which is a cross-sectional survey conducted across India and is nationally representative for all key indicators of women and child health. The main outcome of interest stunting was defined as height-for-age Z-score < −2 SD. Children were classified by living arrangement: with both parents or mother alone. Multivariable logistic regression models were sequentially adjusted for child, maternal, household, and community-level factors. Furthermore, Fairlie decomposition analysis quantified the contribution of observed characteristics to stunting disparities.ResultsA total of 1.35% of children lived with their mother alone, among whom stunting prevalence was significantly higher (39.8%) compared to those with both parents (35.43%). In unadjusted models, child with mother alone was associated with 21% higher odds of stunting (OR: 1.21; 95% CI: 1.12–1.30). However, this association gradually weakened after accounting for confounders in the fully adjusted model (OR: 1.07; 95% CI: 0.97–1.18). Fairlie decomposition (model III) revealed that 70.19% of the stunting gap was attributable to observed factors. Household wealth was the largest contributor (28.29%), followed by maternal height (24.23%) and social caste (13.01%), indicating that structural inequities, rather than the family structure per se, drive the observed disparity.ConclusionThe elevated stunting risk among children living with mothers alone is not intrinsic to single-mother households but is largely associated by socioeconomic disadvantage, maternal undernutrition, and systemic inequities. Policies targeting poverty reduction, maternal health, and education are essential to address stunting in vulnerable family settings.